RESEARCH AND PRACTICE IN STATISTICAL APPLICATIONS TO ACCOUNTING, AUDITING, AND MANAGEMENT CONTROL. - Trueblood, Robert M.; Cooper, W. W. (The Accounting Review, 1955)
Abstract The article discusses the application of statistical methods to accounting, auditing, and management control problems. It is part of a study in this area by a small group in Pittsburgh. The group, consisted of accountants and statisticians who reflect both academic and practicing points of view. The article reports on the progress of the work, and invites suggestions and appraisals from members of the accounting profession. The article focuses on the organization and general approach of the research, studies completed or under way, together with results achieved, and possible directions for future work. The significant points include the importance of the team approach, the need for obtaining guidance from fundamental requirements of accounting and auditing, and the necessity for proceeding in a fashion which protects the professional integrity of the statistician, as well as that of the accountant. The more rapid progress achieved in the areas of accounting procedures and management control devices, as contrasted with purely audit problems, has been specifically noted.